The effect of plyometric training volume on jumping performance - Ebben, W. P.; Suchomel, T. J.; Garceau, L. R. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
This study compared high and low daily volume periodized plyometric training programs and their effect on countermovement jump (CMJ) performance over a 2 week testing time course after training. Thirty-five male subjects participated. Subjects CMJ was tested on a force platform prior to and at 2, 6, 10 and 14 days post training. Peak vertical ground reaction force (GRF), reactive strength index-modified (RSI mod), jump height (JH), and body mass were assessed. No differences were found between the high and low volume training groups. Subjects GRF, RSI mod, and JH performance was improved in a range of 6 to 14 days post- training. Low and high volume periodized plyometric training programs produced equal results. Six to 14 days of recovery post training was required to accrue the training benefit.